Sugar content evaluation in commercially available lidah kucing pastries: uv-vis spectrophotometric analysis of traditional indonesian confections in pontianak tenggara district - Reynaldi, Muhammad Andre; Enggy Erwansani; Hakim, Aditia Rahman; Arif Setiawansyah; Valentina, Febriani; Salsabila, Salwa; Amelia, Nanda; Jaya, Farrel Septian; Agnesia, Agnesia (Sasambo Journal of Pharmacy, 2025)
Glucose content in confectionery products requires careful monitoring due to its association with serious health conditions including obesity, diabetes, and cardiovascular disease. This study examined glucose levels in three lidah kucing cookie samples from Pontianak Tenggara district retailers to assess nutritional variability in these traditional Indonesian confections. The research employed a dual analytical approach combining qualitative and quantitative methods. Initial screening utilized Fehling and Benedict reagent tests to confirm glucose presence, followed by precise quantitative analysis using the Nelson-Somogyi method with UV-visible spectrophotometry. The quantitative protocol involved standard solution preparation, calibration curve development, optimal wavelength determination, and triplicate sample measurements to ensure analytical reliability. Qualitative testing confirmed glucose presence in all three samples through positive Fehling and Benedict reactions. Quantitative analysis revealed significant concentration variations among products. Sample A contained 0.227 percent glucose, Sample B demonstrated substantially higher levels at 0.993 percent, while Sample C showed minimal glucose content at 0.004 percent. These results indicate considerable variability in glucose concentrations across commercially available lidah kucing products within the study area. The investigation successfully established glucose presence in all examined samples while documenting substantial differences in glucose concentrations among similar commercial products. These findings highlight the importance of analytical monitoring in traditional confectionery items and demonstrate significant nutritional variation among comparable products in local markets. The results provide essential baseline data for consumer awareness and potential regulatory considerations regarding glucose content in traditional Indonesian baked goods, supporting informed dietary choices and public health initiatives.